2007
DOI: 10.1080/14734220701286195
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar contributions to verbal working memory: beyond cognitive theory

Abstract: Neuropsychological findings together with recent advances in neuroanatomical and neuroimaging techniques have spurred the investigation of cerebellar contributions to cognition. One cognitive process that has been the focus of much research is working memory, in particular its verbal component. Influenced by Baddeley's cognitive theory of working memory, cerebellar activation during verbal working memory tasks has been predominantly attributed to the cerebellum's involvement in an articulatory rehearsal networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 68 publications
4
77
0
2
Order By: Relevance
“…However, recent morphometric findings in HD patients suggest that the cerebellum is affected over time [Ruocco et al, 2007], and thus could already be involved in the cognitive clinical manifestations of the disorder in an early stage. Apart from its contribution to motor coordination and control, there is increasing neuropsychological and functional imaging evidence that the cerebellum is involved in human cognition [Ben-Yehudah et al, 2007;Fiez, 1996]. Specifically, an emphasis has been placed on cerebellar contributions to articulatory rehearsal processes subserving verbal WM function [Ben-Yehudah et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent morphometric findings in HD patients suggest that the cerebellum is affected over time [Ruocco et al, 2007], and thus could already be involved in the cognitive clinical manifestations of the disorder in an early stage. Apart from its contribution to motor coordination and control, there is increasing neuropsychological and functional imaging evidence that the cerebellum is involved in human cognition [Ben-Yehudah et al, 2007;Fiez, 1996]. Specifically, an emphasis has been placed on cerebellar contributions to articulatory rehearsal processes subserving verbal WM function [Ben-Yehudah et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its contribution to motor coordination and control, there is increasing neuropsychological and functional imaging evidence that the cerebellum is involved in human cognition [Ben-Yehudah et al, 2007;Fiez, 1996]. Specifically, an emphasis has been placed on cerebellar contributions to articulatory rehearsal processes subserving verbal WM function [Ben-Yehudah et al, 2007]. In HD patients, this mechanism might become Results of the between-group ANCOVA, P < 0.001 (familywise error corrected at the voxel level, P < 0.05 corrected for spatial extent).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Broca's area (which overlaps with our left ROI in VLPFC) and left SMA are anatomically interconnected with right lobule VI and crus1 of the cerebellum (37,38). The unilateral activation pattern of VLPFC, SMA, and cerebellum could reflect subvocal rehearsal during the maintenance phase of the verbal and object WM tasks (21,39). Moreover, PMv showed stronger activation in the left hemisphere than in the right across all three investigated WM domains and in both age groups, a pattern consistent with the idea that left PMv plays a role in language (40).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the medial temporal lobe, the cerebellum is also involved in memory processing. [2][3][4]7,33,37,40) Delayed recall of verbal and visual information will be frequently impaired after subtentorial strokes. 18) However, the present study showed that retraction of the temporal lobe caused a decline in temporary short-term memory but the lateral suboccipital approach did not.…”
Section: Discussionmentioning
confidence: 99%
“…21,22,39) Recent clinical, experimental, and neuroimaging studies have indicated that the cerebellum is involved in various neural processes of the higher brain functions such as language, working memory, executive function, and emotion. [2][3][4]7,12,17,18,25,33,34,37,40) Therefore, both neurological status and higher brain function must be maintained after skull base surgery. Cognitive impairment is a common consequence of infratentorial stroke, 18,25) and the neuropsychological outcomes after neurosurgical procedures for unruptured aneurysms have been investigated.…”
Section: Introductionmentioning
confidence: 99%